DPP-4 Inhibitors as Treatments for Type 1 Diabetes Mellitus: A Systematic Review and Meta-Analysis - Qixian Wang; Min Long; Hua Qu; Rufei Shen; Rui Zhang; Jing Xu; Xin Xiong; Hui Wang; Hongting Zheng (Journal of Diabetes Research)
Objective. Several clinical studies have reported the application of dipeptidyl peptidase-4 (DPP-4) inhibitors as treatments for type 1 diabetes mellitus (T1DM). This study aims to review the outcomes of these existing studies and to discuss the therapeutic effects of DPP-4 inhibitors on T1DM. Methods. We thoroughly searched the Medline, Embase, PubMed, and Cochrane Library databases and ClinicalTrials.gov for studies concerning the use of DPP-4 inhibitors in patients with T1DM. Results. In preclinical trials, DPP-4 inhibitors improved the pathogenesis of T1DM. However, only a portion of the studies showed potential efficacy regarding clinical glycemic control and other clinical parameters. From this meta-analysis, pooled data from 5 randomized controlled trials revealed that the additional use of DPP-4 inhibitors resulted in a greater decrease in glycated hemoglobin A1c (HbA1c) levels (0.07%, 95% CI (−0.37%–0.23%)) than insulin monotherapy, although the decrease was not significant. A small decrease in postprandial glucose or insulin consumption was confirmed. Conclusion. Although DPP-4 inhibitors may be beneficial for T1DM, existing studies do not strongly support these positive effects in clinical practice. Further optimized clinical trials are needed.